P-006 The 'hub-spoke' telemedicine model in a large cohort of stroke patients. (23rd July 2022) - El Naamani, K; Herial, N; Abbas, R; Sioutas, G; Amllay, A; Munoz, A; Sweid, A; Morse, C; Moylan, D; Joffe, D; Knapp, M; Tjoumakaris, S; et al.
Abstract : Objectives: Stroke is a leading cause of death and disability worldwide. According to the World Health Organization, stroke patients should be treated in dedicated stroke units. However, stroke units require multidisciplinary stroke expertise which are usually scarce in rural areas. The aim of this study is to assess the efficacy and describe the outcomes of our institution's experience with the tele-stroke network. Methods: This is a retrospective single center study encompassing patients suffering from strokes and receiving pre-hospital and in-hospital tele-stroke expertise based on a spoke/hub stroke network. Data from 38 hospital network between December 2014 and January 2018 were collected. Results: The study cohort consisted of 9702 patients. The majority were females (n= 3556, 55.3%) and the mean age was 67 (67 ± 16.7, 66.7 – 67.4, 26 -122). Of all patients, tissue plasminogen activator (tPA) was recommended in 1313 (16.3%) patients, and from these, 810 (61.7%) patients were actually given tPA. As for endovascular intervention, only 187 (2.3%) patients underwent mechanical thrombectomy at our institution. Conclusion: Tele-stroke networks have proven to be a pivotal development in the treatment of strokes, especially those that are remote. With the additional expertise and the shorter duration from onset to diagnosis to treatment, these networks have substantially improved patient care and decreased healthcare costs, avoiding unnecessary transfers from spoke hospitals to hub. Disclosures: K. El Naamani: None. N. Herial: None. R. Abbas: None. G. Sioutas: None. A. Amllay: None. A. Munoz: None. A. Sweid: None. C. Morse: None. D. Moylan: None. D. Joffe: None. M. Knapp: None. S. Tjoumakaris: 2; C; Microvention, Medtronic. M. Gooch: 2; C; Stryker. R. Rosenwasser: None. P. Jabbour: 2; C; Microvention, Medtronic, Balt, Cerus Endovascular.